Potential Search: A New Greedy Anytime Heuristic Search - Stern, Roni; Puzis, Rami; Felner, Ariel (Proceedings of the International Symposium on Combinatorial Search, 2010)
In this paper we explore a novel approach for anytime heuristic search, in which the node that is most probable to improve the incumbent solution is expanded first. This is especially suited for the "anytime aspect" of anytime algorithms - the possibility that the algorithm will be be halted anytime throughout the search. The potential of a node to improve the incumbent solution is estimated by a custom cost function, resulting in Potential Search, an anytime best-first search. Experimental results on the 15-puzzle and on the key player problem in communication networks (KPP-COM) show that this approach is competitive with state-of-the-art anytime heuristic search algorithms, and is more robust.